National Courts and Preliminary References to the Court of Justice - Krommendijk, Jasper (Edward Elgar Publishing, 2021)
This book has attempted to answer four questions relating to the different phases in the interaction between national courts and the ECJ in the context of the preliminary ruling procedure: question, answer and follow-up. The fourth question concerned the relationship between the answer (ie, the satisfaction of national judges with their interaction with the ECJ and the answers) and the question (ie, the motives of judges (not) to refer).